FEATURES OF BULLYING: https://doi.org/10.5281/zenodo.14842206 - Munarova, Rano (Journal of Contemporary World Studies, 2025)
This article examines the features of bullying among boys, its psychological causes and consequences, and offers recommendations for the prevention and correction of this phenomenon, as well as the specific psychological features of bullying among girls, who are often subjected to special forms of aggression and pressure, as well as the causes, forms, consequences, and possible ways of prevention and correction.